Tagging of the type three secretion system basal apparatus of Enterohaemorrhagic Escherichia coli 0157:H7 - Emmerson, James Robin (The University of Edinburgh, 2008)
Like many Gram negative bacterial pathogens Enterohaemorrhagic Escherichia coli (EHEC) O157:H7 possesses a type III secretion system (T3SS). The T3SS translocates effector proteins into host cells during infection and consists of a basal apparatus that spans the inner and outer membranes and a needle and filament complex. The basal apparatus is composed of -20 proteins that are highly conserved between bacterial species, but despite this homology little is known about the EHEC basal apparatus.

The aim of this project was to label inner membrane basal apparatus proteins with fluorescent markers or immunogenic tags in order to investigate their function, regulation and localization. Cloning strategies were designed to insert tags at the 3' end of eight genes encoding putative inner membrane proteins and to use these fusions to replace the wild type sequences by allelic exchange.

From the eight strategies, escR and escU were taken forward to produce five EHEC O157:H7 strains. One strain contained EscR labelled at the C- terminus with an HA (haemagglutinin) epitope tag and the other four strains contained different labelled versions of EscU. Work with these strains demonstrated that the T3SS could not be visualized using fluorescence microscopy. However, Western blot analysis did show that the EscU protein was cleaved into 30kDa and 10kDa peptides, both of which localized to the membrane fraction of the bacterial cell. This cleavage was most likely occurring at the conserved cleavage site NPTH, which is present in the homologous proteins YscU from Yersinia pseudotuberculosis and FlhB from the flagella basal apparatus of Salmonella Typhimurium.

Interestingly all the mutant strains constructed did not secrete a detectable level of EspD, apart from one fusion that had previously been shown to cleave the tag from EscU. This indicated that, despite the small size of the HA tag, all the tags interfered with the function of EscR or EscU. Fusions to the 10kDa fragment of EscU, along with a deletion of this domain, were used to elucidate its function in the T3SS. All the EscU mutants did not form EspA filaments, secrete EspD at wild type levels or secrete detectable levels of Tir, while the expression from the LEE1 -5 promoters remained unaffected. These phenotypes could not be restored upon supplying the 10kDa peptide in trans.

Based on these results and previous work with the EscU homologues; it is proposed that the uncleaved EscU protein is needed to secrete EscF. After a defined period EscU is cleaved (possibly auto -catalytically) and this allows the secretion of EspA, B and D. The lack of wild type EscU in the mutant strains may not allow EscF to be secreted or assembled correctly and this in turn leads to the inhibition of EspA, B and D translocation.

An anti EscF antibody was obtained and used to detect EscF in cell fractions of the mutant EscU strains. Western blot analysis with this antibody detected a protein of the estimated size for EscF; however, similar size bands were still detectable in a LEE4 deletion strain (containing no escF). Progression of the research requires EscF secretion to be measured in order to establish whether the carboxy -terminal of EscU is essential for EscF export in EHEC O157:H7.

In conclusion, the project utilized a complex strategy to produce single copy gene fusions to basal apparatus proteins. This approach was taken to elucidate the function, localization and interactions of basal apparatus proteins whilst causing minimal changes to sequence, expression and copy number. Even so, it was evident that even minimal changes were not tolerated and inhibited secretion by the system. Future research will have to proceed with either alternative target proteins or the generation of high affinity antibodies coupled with sensitive imaging technology.